PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, IKLIM ORGANISASI DAN WORK ENGAGEMENT TERHADAP JOB CRAFTING KARYAWAN - Muhammad Arvan Marcellino; Surahman Pujianto (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study was to examine and analyze the effect of Transformational Leadership Style, Organizational Climate, and Work Engagement on Job Crafting of PT. Bumen Redja Abadi Tebet Branch. The sample selected for research amounted to 66 employees using a non-probability sampling technique with the sampling method used was the purposive method. Where the data collection technique is using a questionnaire. Research data is processed with WarpPLS 7.0 as a test tool. The results obtained from the study indicate that the Transformational Leadership Style and Organizational Climate, have a significant influence on Work Engagement and Work Engagement significantly on the Job Crafting of employees.. Transformational leadership style has no significant effect on Job Crafting and there is no mediation while Organizational Climate has a significant effect on Job Crafting but there is no mediation.